Juridical Analysis of The Job Creation Law Based On The Theory of Legal Development Related To Investment Policy In The Regions - Elly Kusbandini; Endro Tri Susdarwono (Jurnal Hukum dan HAM Wara Sains, 2022)
The government's focus in the field of regulation is to simplify various regulations and carry out several deregulations. Based on this, the government views that the implementation of the omnibus law can accelerate the simplification of regulations. It is known that investment or investment has an important role for the progress of a country or region. This is because investment is one of the sectors that can be used as a mainstay in increasing Regional Original Income. This study aims to conduct research on the juridical analysis of employment copyright laws based on the theory of legal development related to investment policies in the regions for case studies in Tegal Regency. This research includes normative legal research using primary and secondary data. The type of legal research is a comprehensive analytical study of primary legal materials and secondary legal materials. This study concludes that the Regional Government has the authority to provide investment administration services as stated in Law Number 32 of 2004 Article 14 paragraph (1) letter n. The forms of regional government authority in providing investment administration services include: a. Regulation, namely the making of Regional Regulations concerning Investment/Investment. b. Legalization, namely the granting of permits regarding investment/investment. c. Supervision/Control of the implementation of Investment/Investment d. Giving Sanctions/Awards to Business Entities/Investors. The Omnibus Law on Job Creation has several deeper corrections, especially in terms of the paradigm and substance of regulations regarding layoffs, permits, and regional autonomy (decentralization), but the law instead creates derivative rules which makes more and more new rules appear.